Computer-mediated group communication and ideation performance - Leif Jarle Gressgård (International Journal of Business Science & Applied Management (IJBSAM), 2012)
Computer-based group idea generation is used in a variety of organizational settings to generate ideas that are helpful in attaining a goal. In such situations, the characteristics of the interaction may impact on the group processes, and accordingly on group performance. This paper reports on a study investigating the impacts of synchronicity, parallelism and identification on ideation performance. The results show that both parallelism and synchronicity are important for ideation performance, but that the levels of these affordances have no impacts when it comes to generation of low quality ideas. However, as the quality criteria are sharpened, the importance of the affordances increases. The results thus show that high degrees of parallelism and synchronicity are important for generation of high-quality ideas in computer-mediated group work. The results also point to the importance of adopting rigorous measures when investigating group ideation performance. Implications for research and practice are discussed.
Keywords: 650; ideation; computer-mediated communication; electronic brainstorming; virtual groups; idea quality